Phytoplankton as Bioindikator of Water Quality in The Batu Dendeng River West Lombok - Afiatul Hafifah; Agil Al Idrus; Lalu Japa (Jurnal Biologi Tropis, 2023)
This exploratory descriptive study with a qualitative approach was aims to analyze the water quality of the Batu Dendeng River in West Lombok through a study of the phytoplankton community structure. Sampling was carried out using purposive sampling method. Water sampling was carried out using plankton net of 20µ mesh sized. Observation and identification of phytoplankton was carried out at the Biology Laboratory of FKIP University of Mataram using a binocular microscope. Phytoplankton data was analyzed based on abundance, species diversity, species uniformity and species dominance indexs. The results showed that the community structure of identified phytoplankton in the Batu Dendeng River consisted of 5 classes and 52 species with abundance value of 714.074 (ind/L). Phytoplankton species diversity, uniformity, and dominance indexs of Batu Dendeng River were 2.591, 0.66, and 0.13 respectively. The water pollution criteria based on the diversity index of phytoplankton species, indicates the water quality of the Batu Dendeng River West Lombok was in the slightly polluted category.